Taller Regional de Mejoramiento de Frijol (El Manejo Práctico de Programas de Mejoramiento Genetico) . Trabajos presentados - Dessert, M. (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
A Regional Bean Breeding Workshop was carried out in July 1989 at the Instituto de Ciencia y Tecnologia Agricolas (ICTA) in Jutiapa, Guatemala, to analyze practical managerial aspects of the Regional Cooperative Bean Program for Central America, Mexico, and the Caribbean. This program is financed by the Swiss Development Corporation and CIAT provides support by coordinating the different scientific disciplines involved in the research activities. Workshop objectives were to (1) identify, as a group, the bases to successfully develop a breeding program, (2) determine aspects related to planning, organization, and everyday tasks involved in the management of the program, and (3) promote greater participation/autonomy of the national breeding programs. (CIAT)